Natural and disease-specific autoantibodies in chronic obstructive pulmonary disease - Daffa, N.I.; Tighe, Patrick J.; Corne, J.M.; Fairclough, Lucy C.; Todd, Ian (Wiley, 2014)
Autoimmunity may contribute to the pathogenesis of chronic obstructive pulmonary disease (COPD). Studies have identified disease-specific autoantibodies (DSAAbs) in COPD patients, but natural autoantibodies (NAAbs) may also play a role. Previous studies have concentrated on circulating autoantibodies, but lung-associated autoantibodies may be most important. Our aim was to investigate NAAbs and DSAAbs in the circulation and lungs of COPD smoking (CS) patients compared to smokers (S) without airway obstruction and subjects who have never smoked (NS). Immunoglobulin (Ig)G antibodies that bind to lung tissue components were significantly lower in the circulation of CS patients than NS (with intermediate levels in S), as detected by enzyme-linked immunosorbent assay (ELISA). The levels of antibodies to collagen-1 (the major lung collagen) detected by ELISA were also reduced significantly in CS patients’ sera compared to NS. The detection of these antibodies in NS subjects indicates that they are NAAbs. The occurrence of DSAAbs in some CS patients and S subjects was indicated by high levels of serum IgG antibodies to cytokeratin-18 and collagen-5; furthermore, antibodies to collagen-5 eluted from homogenized lung tissue exposed to low pH (0·1 M glycine, pH 2·8) were raised significantly in CS compared to S and NS. Thus, this study supports a role in COPD for both NAAbs and DSAAbs.